INTERDISCIPLINARY ACTIVITY TRAINING IN VIRTUAL ENGINEERING ENVIRONMENT: AN ACTUAL STATE AND PROSPECTS - V. S. Sheinbaum (Высшее образование в России)
The paper considers two aspects of the problem of multidisciplinary education: the first, as an effective interaction between business and academic communities to establish a new normative base for qualifications; and the second, as a purely educational problem that can be solved by using a complex of approaches, as Gubkin University’s experience shows. These approaches include: creating the special environment (infrastructure) of interdisciplinary education such as the virtual organization representing a network of computerized workstations and training facilities for specialists and operators of various professions as well as digital models of work objects and means; designing of scenarios for multidisciplinary training for various types of multidisciplinary activities such as research, design, diagnostics, and management of technological processes; identifying, within the core curricula programs (CCP) of educational institutions, the disciplines or courses delivered in the multidisciplinary format and synchronized for different CCP through course scheduling.